2022
DOI: 10.1111/ejss.13291
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of vineyard soils derived from Plio‐Quaternary landforms (raña or rañizo) in southern Europe

Abstract: Soil is an essential component in viticulture. The study reported here concerns the assessment of the morphology chemical and physicochemical features of typical, well‐developed and representative evolved Mediterranean soils near Anchuras (Spain, southern Europe), a site with soils that developed on old landforms (Plio‐Quaternary) called ‘raña’ and/or ‘rañizo’. The soils under study were described and sampled by conducting soil surveys. Selected soil properties, such as texture, bulk density, pH, electrical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…With the addition of compost (with basic pH) to the vineyard soils for two years, the pH of these soils increased to neutral values. Different authors have indicated that the pH of vineyard soils can be from acidic (pH < 5.5) to basic soils (pH 8.5), although in terms of vine cultivation, a neutral pH is preferable [60][61][62][63][64]. In our study, the treatment with compost had a positive effect on the soils of both plots, increasing the pH and favoring the maintenance of the soil pH at neutral values, so its regular use is recommended for this slightly acidic soil.…”
Section: Discussionmentioning
confidence: 99%
“…With the addition of compost (with basic pH) to the vineyard soils for two years, the pH of these soils increased to neutral values. Different authors have indicated that the pH of vineyard soils can be from acidic (pH < 5.5) to basic soils (pH 8.5), although in terms of vine cultivation, a neutral pH is preferable [60][61][62][63][64]. In our study, the treatment with compost had a positive effect on the soils of both plots, increasing the pH and favoring the maintenance of the soil pH at neutral values, so its regular use is recommended for this slightly acidic soil.…”
Section: Discussionmentioning
confidence: 99%